New rodent faunas from Middle Miocene and Mio- Pliocene in the Cabriel Basin (Valencia, Spain) - Ruiz-Sánchez, F.J.; Santisteban, C.; Crespo-Roures, V.D.; Freudenthal, M. (Journal of Iberian Geology, 2011)
Five new localities with micromammal remains have been located in the Cabriel Basin. These localities are situated in the eastern area of the Cabriel Basin, in the Juan Vich ravine, where the oldest deposits of this basin crop out. The localities JV2, JV3 and JV6 are of Middle Miocene age, JVTLI1 of Middle Miocene or Late Miocene age and JVTS1 of Late Miocene or Early Pliocene age. The beginning of the sedimentary history of the basin was attributed to Late Turolian (Late Miocene). The new sedimentary record from the Juan Vich ravine and the mammalian findings extend the stratigraphic and paleontological knowledge of the Basin.